2009
DOI: 10.1007/s15010-008-8194-9
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B virus infection in a Cohort of HIV-positive patients: Correlation with hepatitis C virus coinfection, virological and immunological features

Abstract: In relation to the high prevalence of occult HBV infection, particularly in HIV/HCV-coinfected individuals, it is necessary to clarify the clinical impact of this cryptic infection by monitoring HBV-DNA in plasma using the correct approach. Similarly to HBsAg-positive individuals of the Mediterranean area, HBV genotype D is invariably detected in this cohort of HIV-infected patients with occult HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
39
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 29 publications
8
39
4
2
Order By: Relevance
“…OBI may also be observed in anti-HIV-positive patients with chronic HBV/HCV coinfection, due to an HBsAg serum clearance consequent to a strong inhibitory effect of the HCV genome on HBV replication [103] . In HIV subjects a strong association between OBI and HCV infection has been observed in several studies [28,101,[104][105][106] . In contrast, Jardim et al [107] reported no significant difference in the rate of OBI in HIV-positive patients with or without HCV coinfection.…”
Section: Epidemiology Of Obi In Hiv-positive Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…OBI may also be observed in anti-HIV-positive patients with chronic HBV/HCV coinfection, due to an HBsAg serum clearance consequent to a strong inhibitory effect of the HCV genome on HBV replication [103] . In HIV subjects a strong association between OBI and HCV infection has been observed in several studies [28,101,[104][105][106] . In contrast, Jardim et al [107] reported no significant difference in the rate of OBI in HIV-positive patients with or without HCV coinfection.…”
Section: Epidemiology Of Obi In Hiv-positive Subjectsmentioning
confidence: 99%
“…The clinical value of these data should be confirmed in larger studies, but they suggest that the detection of HBV DNA in PBMC offers a useful tool to identify OBI. Morsica et al [104] analyzed 1593 anti-HIVpositive patients enrolled in the Italian Cohort of Antiretroviral Naïve patients and found 175 (11%) HBsAgnegative/anti-HBc-positive patients: 27of these 175 (15%) patients had detectable HBV DNA in plasma. This prevalence was significantly higher (21%) in the 101 anti-HCVpositive than in the 74 (8%) anti-HCV-negative, regardless of the immune status, HIV load, or ART regimen.…”
Section: Epidemiology Of Obi In Hiv-positive Subjectsmentioning
confidence: 99%
“…However, studies have shown that HBVdeoxyribonucleic acid (HBV-DNA) can be detected in patients with serological profi les that would traditionally be interpreted as previously infected or never infected 16,40 and in patients who are also seropositive for anti-HBc 41 . The prevalence of occult hepatitis B infection in HIV-positive patients with isolated anti-HBc ranges from 0% to 89% 42 .…”
Section: Informed Written Consent Was Obtained From All Participantsmentioning
confidence: 99%
“…In those cases with detectable HBV DNA, levels rarely reach 350 IU/ mL. [2][3][4][5][6][7][8][9][10] Then the question is, what is the clinical relevance of these findings? In one of the most recent series published, alanine aminotransferase levels were not higher in the patients found to have ''occult'' HBV infection, 10 nor were patients reported to have developed liver complications.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Then the question is, what is the clinical relevance of these findings? In one of the most recent series published, alanine aminotransferase levels were not higher in the patients found to have ''occult'' HBV infection, 10 nor were patients reported to have developed liver complications. The same authors also analyzed a possible link between occult infection and cellular immunodeficiency, which has been the claimed reason for a higher frequency of this event in HIV-infected patients, but did not find it.…”
mentioning
confidence: 99%